Intravenous immunoglobulin therapy in proximal diabetic neuropathy - Kawagashira, Yuichi (BMJ Publishing Group, 2009)
A 57-year-old man with type 2 diabetes mellitus for 10 years showed progressive loss of muscle strength in both legs, pain and muscle atrophy in the femoral region and significant weight loss. On admission, he could not stand alone and used a wheelchair. He also complained of severe pain in the lower extremities. He was diagnosed with proximal diabetic neuropathy (PDN) by characteristic clinical and electrophysiological features. Intravenous immunoglobulin therapy (IVIg 0.4 g/kg×5 days) markedly reduced the severe pain and muscle weakness in the legs. Eventually, pain assessed by the Visual Analogue Scale was relieved by 80% and muscle strength was also well recovered, thereby enabling the patient to walk with a cane. The present case suggests that IVIg therapy may be effective for the relief of pain in PDN.